Registration of 'CP 11‐1956' sugarcane. Issue 1 (22nd December 2020) - Sandhu, H.S.; Zhao, D.; Davidson, R.W.; Gordon, V.S.; Islam, M.; McCord, P.H.; Sood, S.; Baltazar, M.; Singh, M.P.
Abstract: Sugarcane (a complex hybrid of Saccharum spp.) cultivar 'CP 11‐1956' (Reg. no. CV‐198, PI 695075) was released in June 2018 for commercial cultivation on organic (muck) soils in Florida. This cultivar was developed through a collaborative cultivar development program of the USDA–ARS, the University of Florida, and the Florida Sugar Cane League, based at Canal Point, FL. The parents of CP 11‐1956 are CP 03‐2188 (female) and CP 01‐2459 (male). CP 11‐1956 was released because of its excellent combination of disease resistance against major sugarcane diseases and cane and sugar yields that are similar to reference cultivars that are major commercial cultivars in Florida. CP 11‐1956 is considered resistant to brown rust, orange rust, ratoon stunting disease, smut, and mosaic. This cultivar is also moderately resistant to leaf scald and yellow leaf disease. Cane and sugar yields of CP 11‐1956 are similar to the reference cultivar CP 96‐1252 that has occupied the largest acreage in Florida for several years. CP 11‐1956 had poor freeze tolerance compared with several reference cultivars.